Diabetes and traditional remedies in Medieval Persia: a historical perspective - Safavi, Fereshteh; Andrade-Cetto, Adolfo; Escandón-Rivera, Sonia M. (Frontiers in Pharmacology, 2025)
Traditional Persian Medicine (TPM) has long contributed to the diagnosis, prevention, and treatment of diabetes. Rooted in the theory of temperament, TPM classifies individuals and diseases according to four qualities: warm-dry, warm-wet, cold-wet, and cold-dry. In classical TPM literature, diabetes is referred to by various names—most notably “dhiabitos” and “dulāb”—and is consistently associated with dysfunction of the kidneys and liver. For this study, seminal TPM texts were systematically reviewed using targeted keywords to extract definitions, etiologies, symptoms, diagnostic criteria, and therapeutic strategies related to diabetes. These findings were supplemented with data from electronic databases, including ScienceDirect, PubMed, and Scopus. TPM classifies diabetes into two categories: hot and cold. Historical manuscripts detail a wide array of therapeutic preparations, predominantly herbal and herbo-mineral formulations, along with several mineral substances believed to balance temperament. Among these, oral dosage forms, particularly Safoofs (dry powders), were the most frequently prescribed across both categories. In total, 208 plant species from 81 botanical families, along with several mineral substances, were identified in traditional formulations. According to TPM, the medicinal plants, similarly to diseases, commonly exhibit either hot or cold properties, reflecting the principle that treatments should rebalance underlying dystemperament rather than merely relieve symptoms. This paradigm emphasizes addressing the root causes of disease. TPM physicians (hakims) often attribute diabetes to factors such as kidney dysfunction and dysregulated water metabolism. In contrast, modern biomedical literature does not distinguish between “hot” and “cold” diabetes; these classifications may reflect two stages in the spectrum of diabetes pathology. Hot diabetes may align with the early stages of Type 2 diabetes, while cold diabetes corresponds to the advanced stages of Type 2 diabetes or possibly Type 1 diabetes. Future research should examine the phytochemical and pharmacological profiles of plants used in the treatment of “hot” and “cold” diabetes, with a particular emphasis on their hypoglycemic properties. Plants used for “hot” diabetes may possess anti-inflammatory effects that protect pancreatic beta cells and improve insulin function. Additionally, it is important to explore the potential effectiveness of plants associated with “cold” diabetes in managing diabetes-related complications, such as nephropathy.